Development of Loop-Mediated Isothermal Amplification Assay for Rapid Detection and Analysis of the Root-Knot Nematode Meloidogyne hapla in Soil - Zahra Saad Omer; Ann-Charlotte Wallenhammar; Maria Viketoft (Horticulturae, 2022)
Soil analysis is crucial for estimating the risk of crop damage by the root-knot nematode Meloidogyne hapla. Here, we developed an analysis assay based on Loop-mediated Isothermal Amplification (LAMP). The LAMP primers were verified for specificity against 10 different nematode species. A manual soil DNA extraction, referred to as SKMM, was developed and compared with a FastDNA kit followed by DNA purification. DNA was extracted with both methods from artificially inoculated soils as well as from naturally infested soil collected from farm fields. The primers exclusively amplified DNA from M. hapla with both colorimetric and real-time LAMP. The detection limit was 193 gene copies and 0.0016 juveniles (12 pg µL−1) per reaction. DNA concentrations and purity (A260/A230) were significantly higher using the SKMM procedure compared with the kit. From the field samples collected in 2019, DNA was amplified from 16% of samples extracted with SKMM and from 11% of samples using the kit. Occurrence of M. hapla DNA was confirmed in soil samples from two out of six field soils in 2020 using both real-time LAMP and qPCR. In conclusion, the developed real-time LAMP is a fast and specific assay for detection and quantification of M. hapla DNA in soil.